NOTARIS DAN ASAS KEBEBASAN BERKONTRAK DALAM PPJB RUMAH SUSUN - Edward Sardono Tedjosaputro (JURNAL ILMIAH HUKUM DAN DINAMIKA MASYARAKAT, 2021)
One of the primary human needs for survival is a place to live or a house. Withthe limited land available and the increasing population, the type of house such as flats can be an option for Indonesians to get a place to live. With the rampant construction of flats, the government issued Law No. 20 of 2011 concerning Flats to regulate problems in flats. The law states that the Sale and Purchase Agreement (PPJB) can be made in the presence of a notary before the construction process is complete. However, there are conditions that must be met in making PPJB such as the existence of an IMB. In reality, there is a notary who makes PPJB even though the IMB does not exist based on the principle of freedom of contract. The absence of an IMB was included as one of the clauses in the PPJB. On this occasion, the author is interested in seeing how the notary's role in making PPJB is related to the principle of freedom of contract. This research was conducted using the normative juridical method, which was carried out by examining library materials obtained from various sources such as literature, laws and regulations, and the internet which were collected and analyzed. Based on the literature study that has been done, it can be seen that in the principle of freedom of contract there are limitations that should not be violated. One of the limitations in the principle of freedom of contract is that it cannot conflict with existing laws and regulations. Therefore, notaries as representatives of the state have an active role in making PPJB. In relation to the principle of freedom of contract, the notary must adhere to the applicable law and should inform interested parties about the requirements that must be met in making PPJB and ensure that all requirements have been met before PPJB is made.